Economic Growth and Unemployment: An Empirical Analysis of Okun’s Law in the Case of Libya - Dr. Mustafa S Almajdob; Dr. Osama Dawo Omran Ibrahim (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
In the past ten years, unemployment has increased in the majority of North African nations. Libya is experiencing a low employment rate and a high population increase. According to Okun’s law, there is a negative correlation between economic growth and the unemployment rate. This study aims to evaluate Okun’s law’s applicability in Libya. We employed the Granger causality test framework of the vector autoregressive (VAR) model to assess the causal relationship between the variables and investigate the relationship between the unemployment rate and economic growth. Granger’s causality test results show that GDP rate is Granger-caused, and the causation path is from GDP rate to the unemployment rate. the unemployment rate does not cause GDP Rate, because of the p-value (0.106 > 0.05).